From the editors - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
From the Editors TEACHING AND ASSESSING LISTENING SKILLS EFFECTIVELY IN THE LANGUAGE CLASSROOM: RESEARCH-BASED APPROACHERS As stated in the last volume of the International Journal of Listening, "Compared with the other L2 skills of reading, writing and speaking, the field of listening is the youngest in terms of research" (Goh and Aryadoust, 2016: 6). This youth of listening skills development in the field of language teaching is partly due to availability of technological advances (audio recordings and videos) and (computer-based) teaching materials which were introduced at a later date in the classroom than paper-based materials. But a slower development of listening skills research is also determined by the fact that listening is a complex skill: it requires attention and concentration, it demands an instant recognition of an event and its related keywords, since vocabulary control and schemata knowledge (situation, topic knowledge and background knowledge) under which the listening input takes place are key factors in determining effective listening. Not only that, speaker factors (accent, intonation) and individual listener factors such as the listening strategies employed by an individual, gender or anxiety levels, are part of the listening skills construct. When we talk about assessing listening skills, together with these issues there is the question of task format in relation to both input and output requirements, the types of questions used in assessing listening skills or the number of times students are allowed to listen to a (video/audio) recording. All these aspects of listening make research in listening an intellectually and academically challenging work.